Place leadership and corporate spatial responsibilities - Hans-Hermann Albers; Lech Suwala (Handbook on City and Regional Leadership, 2021)
The management of urban and rural areas has always consisted of a mixture of state, market and civil society actors. In times of increased liberalization, deregulation and privatization of many former state-dominated tasks, limited institutional capabilities of smaller communities, a lack of consolidated government bodies and low effectiveness of authorities, there exists a greater interest for non-state `place-based' economic engagement in general, and for private-sector involvement and leadership in regional governance in particular. This chapter introduces approaches to enterprise-driven urban and regional engagement. Empirically, the chapter summarizes existing case studies from the literature on enterprise-driven urban and regional engagement and asks if and how place leadership initiatives interact with corporate social responsibilities. In conclusion, the chapter suggests it is desirable to explicitly include the private sector in place leadership roundtables in order to create tri-sectoral negotiations.
Keywords: G34; M14; R38; R58; R11; R12; L52; L53; 330; Place Leadership; Corporate Spatial Responsibility; Regional Development; Corporate Social Responsibility; Urban and Regional Planning; Private-Sector Led Development; Business Improvement Districts; Town-Center Management; Corporate-led Master Plan Initiatives; Space Leadership